Contribution Accounting – a planning and controlling tool to observe costs and profit achievements within management decisions - Marc Milling (ZBW – Leibniz Information Centre for Economics, 2019)
Management decisions must be based on financial data, drawn up by controlling. Especially when it comes to strategic decisions the target is to achieve a comprehensive overview of financial issues like costs and related profits on which to base management decision. In summarisation accountants have not only to collect financial data, they have to contrast costs and benefits as far as risks and opportunities. A clear and transparent contribution accounting should be the central cost controlling instrument, according to business fields and cost centres. So, it is getting possible to ensure that the resources are efficiently allocated as a result of a proper management decision. The following article introduces contribution accounting as an important tool to support management decisions regarding cost planning and cost cutting in educational institutions.
Keywords: M21; 330; Contribution Accounting; Management Decisions